(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The relationship between psychology and pedagogy is most vividly demonstrated in the study of how individuals learn. Theories of learning styles and multiple intelligences offer valuable insights into the diversity of learners’ cognitive, emotional, and behavioral profiles. This paper explores the psychological foundations and pedagogical implications of these theories, emphasizing their application in modern classrooms. It argues that recognizing individual learning differences enhances teaching effectiveness, fosters inclusivity, and promotes lifelong learning skills. The discussion integrates psychological theories, pedagogical practices, and contemporary critiques to form a comprehensive understanding of differentiated instruction.